(untitled) (Oxford, 2000)
This book discusses the state-of-the art in twin and sib-pair analysis of complex disease both from the perspective of epidemiology (study design, subject selection, sampling strategies) and biostatistics (path analysis, survival analysis, linkage analysis, association studies). Novel ways are discussed in which twins and sib-pairs can be used to meet the challenge of identifying the location and function of genes underlying complex traits.
Keywords: Heredity,Diseases in twins,Di truyền,Bệnh tật ở trẻ song sinh; Human,Người